DETERMINANTS OF ACCOUNTING FRAUD LIKELIHOOD - Monday Olade, IZEVBEKHAI (PhD, ACIT); Owa, FREDERICK (PhD, CNA) (Scholar Express Journals, 2024)
This study examined the determinants of accounting fraud likelihood. The secondary source of data collection was adopted in the study where the purposive sampling technique was used to select a sample size of eight (8) listed deposit money banks in Nigeria. Ordinary Least Square regression analysis was used in this study and the findings revealed amongst others that firm leverage has significant effect on fraud likelihood of firms listed on the Nigerian Exchange Group and also, firm growth has effect on fraud likelihood of firms listed on the Nigeria Exchange Group. The study recommended that small number of directors should be avoided so as to minimize the occurrence and cover-up of fraudulent activities.
Keywords: Accounting fraud; firm size; firm growth; firm age